Teacher leadership development: Tracking one district’s progress over three years - Eckert, Jonathan; Daughtrey, Alesha (Education Policy Analysis Archives, 2019)
This study tracks the progress of one Iowa school district over the course of three years through its implementation of a Teacher Leadership and Compensation (TLC) model, designed in response to a statewide TLC system initiative. A survey administered at baseline and at the conclusion of each of three pilot years measured teacher leadership development, identified specific areas for improvements, and guided the district’s teacher leadership support efforts. Scores from the items demonstrated evidence of reliability and district leaders reported that resulting data were beneficial to an implementation plan that yielded increased planned retention and improved practice, two goals for the TLC model. Implications for the use of the survey tool, policy, and practice around teacher leadership development are discussed in the context of the collective leadership of teachers and administrators together.